Genomic Insight into Mechanisms of Reversion of Antibiotic Resistance in Multidrug Resistant Mycobacterium tuberculosis Induced by a Nanomolecular Iodine-Containing Complex FS-1 - Ilin, Aleksandr I.; Kulmanov, Murat E.; Korotetskiy, Ilya S.; Islamov, Rinat A.; Akhmetova, Gulshara K.; Lankina, Marina V.; Reva, Oleg N. (Frontiers in Cellular and Infection Microbiology, 2017)
Drug induced reversion of antibiotic resistance is a promising way to combat multidrug resistant infections. However, lacking knowledge of mechanisms of drug resistance reversion impedes employing this approach in medicinal therapies. Induction of antibiotic resistance reversion by a new anti-tuberculosis drug FS-1 has been reported. FS-1 was used in this work in combination with standard anti-tuberculosis antibiotics in an experiment on laboratory guinea pigs infected with an extensively drug resistant (XDR) strain M. tuberculosis SCAID 187.0. During the experimental trial, genetic changes in the population were analyzed by sequencing of M. tuberculosis isolates followed by variant calling. In total 11 isolates obtained from different groups of infected animals at different stages of disease development and treatment were sequenced. It was found that despite the selective pressure of antibiotics, FS-1 caused a counter-selection of drug resistant variants that speeded up the recovery of the infected animals from XDR tuberculosis. Drug resistance mutations reported in the genome of the initial strain remained intact in more sensitive isolates obtained in this experiment. Variant calling in the sequenced genomes revealed that the drug resistance reversion could be associated with a general increase in genetic heterogeneity of the population of M. tuberculosis. Accumulation of mutations in PpsA and PpsE subunits of phenolpthiocerol polyketide synthase was observed in the isolates treated with FS-1 that may indicate an increase of persisting variants in the population. It was hypothesized that FS-1 caused an active counter-selection of drug resistant variants from the population by aggravating the cumulated fitness cost of the drug resistance mutations. Action of FS-1 on drug resistant bacteria exemplified the theoretically predicted induced synergy mechanism of drug resistance reversion. An experimental model to study the drug resistance reversion phenomenon is hereby introduced.